Love the food that loves you back : 100 recipes that serve up big portions and super nutritious food - Muhlstein, Ilana (Mango Publishing Group, 2024)
Easy recipes for breakfast, lunch, dinner, snacks and desserts that allow you to feel satisfied while you prioritize your health. Don't sacrifice great taste while trying to lose weight.